Protective Roles of Sodium Butyrate in Lipopolysaccharide-Induced Bovine Ruminal Epithelial Cells by Activating G Protein-Coupled Receptors 41 - Yang, Tianyu; Datsomor, Osmond; Jiang, Maocheng; Ma, Xiaoyu; Zhao, Guoqi; Zhan, Kang (Frontiers in Nutrition, 2022)
This study aimed to evaluate whether sodium butyrate (SB) attenuates the ruminal response to LPS-stimulated inflammation by activating GPR41 in bovine rumen epithelial cells (BRECs). We examined the SB regulation of GPR41 and its impact on LPS-induced inflammation using GPR41 knockdown BRECs. The LPS-induced BRECs showed increases in the expression of genes related to pro-inflammation and decreases in the expression of genes related to tight junction proteins; these were attenuated by pretreatment with SB. Compared with that in LPS-stimulated BRECs, the ratio of phosphorylated NF-κB (p65 subunit) to NF-κB (p65 subunit) and the ratio of phosphorylated IκBα to IκBα were suppressed with SB pretreatment. The LSB group abated LPS-induced apoptosis and decreased the expression of Bax, Caspase 3, and Caspase 9 mRNA relative to the LPS group. In addition, the LSB group had a lower proportion of cells in the G0–G1 phase and a higher proportion of cells in the S phase than the LPS group. The mRNA expression of ACAT1 and BDH1 genes related to volatile fatty acid (VFA) metabolism were upregulated in the LSB group compared to those in LPS-induced BRECs. In addition, pretreatment with SB promoted the gene expression of GPR41 in the LPS-induced BRECs. Interestingly, SB pretreatment protected BRECs but not GPR41KD BRECs. Our results suggest that SB pretreatment protects against the changes in BRECs LPS-induced inflammatory response by activating GPR41.